PENGARUH FAKTOR-FAKTOR NON-INTELEKTUAL TERHADAP GEJALA BERPRESTASI KURANG : Studi Terhadap Siswa SMA Proyek Perintis Sekolah Pembangunan - Moh. Surya, - (1979)
At least there are three components involved, namely the learner, the learning process, and the learning Luation producing together achievement. The degree of achievement will depend on the optimal interaction among the factors of the three components, intellectual as well as non-intellectual. Intellectual factors as a potential capacity form the basic pattern of the degree of achievement reached throug learning activities and processes. Non-intellectual factors, internal as well as external, appear to influence the achievement also.Individual differences in the achievement can be explained by the interaction among these factors; when one of the factors is constant, the difference can be explained by the others. In this connection one of the learning problems is underachicvoment which has asso-